Prevalence of sexually transmitted infections among pregnant women with known HIV status and their perinatal outcome- a retrospective single centre analysis - Chaubey, Supriya; Melhotra, Ragini; Sharma, Umesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The objective of this study was to determine the prevalence of sexually transmitted infections (STIs) and other reproductive tract infections (RTIs) among pregnant women and their perinatal outcome. Methods: Pregnant women in their 3rd trimester (N=1000) from September 2009 and august 2010 were included. Information related to demographic profile, obstetrics complications, previous genital infections and gynecological diseases were taken. All pregnant women were followed up for their 4-week perinatal outcome. Results: The prevalence of sexually transmitted infection was 25.2% in pregnant women. The prevalence of HIV, Hepatitis B, HSV2 and HPV infection was 2.3%, 4.2%, 0.6%, 0.1% respectively. Prevalence of infection with C. trachomatis, G. vaginalis, T. vaginalis and C. albicans was 5.8%, 10.2%, 5.2%, 9.5% respectively. The prevalence of infection with N. gonorrhea and T. pallidum was found to be 0. Conclusions: Rates of STIs and RTIs are still high among pregnant women. A declining trend for curable STIs/RTIs (syphilis and gonorrhea) was noted. Perinatal outcome was affected adversely in pregnant women with STIs/RTIs.